Cowpea yield gain from resistance to Striga gesnerioides parasitism in southern Benin - Carsky, R.J.; Akakpo, C.; Singh, B.B.; Detongnon, J. (Cambridge University Press, 2003)
Striga gesnerioides is a serious parasite of cowpea (Vigna unguiculata) on the Abomey plateau of southern Bénin. S. gesnerioides in southern Bénin has been characterized as a race that is different from those found in the dry savanna of West Africa. IITA breeding line IT93KZ-4-5-6-1-5 was used in a trial to study fertilizer response of cowpea on two farmers' fields in 1998. No emerged S. gesnerioides plants were observed on this breeding line while heavy parasite loads were observed on local cultivars growing in adjacent fields. In 1999, IT93KZ-4-5-6-1-5 was grown again on seven fields and no emerged S. gesnerioides plants were observed. In 2000 the same line was grown on 18 farmers' fields with local cowpea cultivars in adjacent control plots. The mean number of S. gesnerioides plants on the local cultivars was 0.92 per cowpea plant (s.d. 0.72) while the improved line carried none. The mean yield gain from the improved cowpea line was 156% and varied from 20 to 680 kg pods ha−1. Thus it appears that progress has been made in developing cowpea lines that are resistant to S. gesnerioides and the potential impact of adoption of resistant cowpea is high.